(untitled) (Research, Society and Development, 2022)
Neonatal sepsis is one of the leading causes of death in newborns. Prior knowledge of risk factors is essential to prevent morbidity and mortality. This study aims to characterize the observed risk factors and their relationship with the occurrence of death in newborns diagnosed with sepsis. A cross-sectional study was carried out with the analysis of 712 participants hospitalized from September 2018 to June 2020. 410 neonates were included, with a higher proportion being males, born with artificial delivery and low birth weight. The prevalence of death observed was 6.3%, occurring especially among those with moderate and extreme prematurity, those born to teenage mothers or mothers over forty, those with hyperthermia, low weight, bradycardia and longer hospital stays. There was a low frequency of blood cultures performed. Although there was no predominance of typical clinical findings of sepsis, such as hypothermia, changes in the leukogram, platelet count and CRP levels, the robust findings of a greater association of extreme low birth weight, hyperthermia and tachypnea to a higher frequency of death reinforce the quality of the data obtained.